Pengaruh Word Of Mouth, Brand Image, Dan Country Of Origin Terhadap Keputusan Pembelian Online Produk Eiger (Studi Kasus Mahasiswa FEB Unisma) - Moh Imron; N Rachma; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study examines and analyzes the effect of word of mouth, brand image, and country of origin on online purchasing decisions of Eiger products. This research uses explanatory research type. The research subjects were carried out on FEB students of the Islamic University of Malang. Malhotra theory is used to take samples, namely the number of items x 5 so that the sample is found as many as 140 people. The data collection method is done by using a questionnaire. The analysis method used is the Validity Test, Realiability Test, Normality Test, Multiple Linear Regression Analysis, Classical Assumption Test, Multicolinearity Test, Heteroscedasticity Test, Determination Coefficient (R2) and Hypothesis Test. The results showed that Word of Mouth, Brand Image and Country of origin had a simultaneous influence on Eiger Product Online purchase decisions, Word of Mouth had an effect on Eiger Product Online purchase decisions, Brand Image had an effect on Eiger Product Online purchase decisions, Country of origin affected Online purchase decisions for Eiger Products. Keywords: Word Of Mouth, Brand Image, Country Of Origin, Purchase Decision